Exploring the effects of dietary methionine supplementation on European seabass mucosal immune responses against Tenacibaculum maritimum - Inês Carvalho; Inês Carvalho; Diogo Peixoto; Diogo Peixoto; Inês Ferreira; Inês Ferreira; Diego Robledo; Diego Robledo; Lourenço Ramos-Pinto; Rodolfo Miguel Silva; José Fernando Gonçalves; Marina Machado; et al. (Frontiers in Immunology)
IntroductionDietary methionine supplementation has been shown to enhance immunity and disease resistance in fish. However, excessive intake may lead to adverse effects. The present study aimed to evaluate the immune status of European seabass (Dicentrarchus labrax) fed increasing levels of dietary methionine supplementation and to investigate the early immune response to Tenacibaculum maritimum.MethodsFor this purpose, juvenile European seabass were fed one of three experimental diets containing methionine at 8.6 mg/g (CTRL), 18.5 mg/g (MET2), and 29.2 mg/g (MET3) for four weeks, followed by a bath challenge with T. maritimum.ResultsWhile higher methionine intake reduced hemoglobin levels, no other significant changes in the immune status were observed. However, after infection, fish fed higher methionine levels exhibited a dose-dependent decrease in the mRNA expression of some proinflammatory genes. Similarly, RNA sequencing analysis of skin tissue revealed an attenuated immune response in the MET2 group at 24 hours post-infection, with few proinflammatory genes upregulated, which intensified at 48 h, potentially due to advanced tissue colonization by T. maritimum. The MET3 group displayed the least pronounced immune response, along with the enrichment of some immune-related pathways among the downregulated transcripts. These findings, together with the lower mRNA expression of proinflammatory genes in the head kidney and the higher mortality rates observed in this group, suggest a potential impairment of the immune response.`DiscussionOverall, these findings indicate that dietary methionine supplementation may significantly influence both systemic and local immune responses in European seabass, highlighting the need for careful consideration when supplementing diets with methionine.